Novel CNGA3 mutations in Chinese patients with achromatopsia. Issue 4 (30th January 2015) - Liang, Xiaofang; Dong, Fangtian; Li, Hui; Li, Huajin; Yang, Lizhu; Sui, Ruifang
Abstract : Objective: To study the clinical features and to identify the pathogenic mutations in Chinese patients with achromatopsia (ACHM). Design: Fifteen patients from 10 unrelated families were included in this study. Detailed ocular examinations were performed for the affected subjects, including best-corrected visual acuity (BCVA), colour vision, slit lamp, fundus, electroretinography, perimetry, and spectral domain optical coherent topography (SD-OCT). Peripheral blood samples were obtained from all of the patients and their family members for genomic DNA extraction. All exons of CNGA3, CNGB3, GNAT2, PDE6C and PDE6H were ampliﬁed by a PCR and screened for mutation by direct Sanger sequencing. The sequences were analysed using the Blat tool and then compared with the gene transcript. A segregation test was conducted in the patients' parents if they were available. The variants were compared with the database of the 1000 Genomes Project to exclude polymorphism. Results: Nystagmus, photophobia, and impaired colour discrimination were observed in all patients. The BCVA of the affected subjects ranged from 0.05–0.2. Severely depressed and non-recordable cone electroretinograms were observed. Noticeable structural changes including disruption or loss of the macular inner/outer segments (IS/OS) junction of the photoreceptors were observed with SD-OCT. CNGA3 mutations were identified in 13 patients from eight families. Sequencing revealed seven novel missense mutations, three novel deletion mutations, and four previously reported mutations among those patients. Conclusions: CNGA3 mutation is the most frequent cause of ACHM in this cohort of patients. Ten novel mutations were identified in CNGA3. Genetic characterisation of patients with ACHM is important for genetic counselling and future gene therapies. This study reports the comprehensive clinical and genetic features of Chinese patients with ACHM.